Adherence to the Dietary Approaches to Stop Hypertension diet reduces the risk of breast cancer: A systematic review and meta-analysis - Shu, Long; Huang, Yi-Qian; Zhang, Xiao-Yan; Zheng, Pei-Fen; Zhu, Qin; Zhou, Jian-Ying (Frontiers in Nutrition, 2023)
Background: Despite increasing evidence for the association of adherence to the Dietary approaches to stop hypertension (DASH) diet with breast cancer risk, the results remain inconclusive. The purpose of the current systematic review was to summarize the evidence from previous observational studies and explore the potential association between DASH diet and breast cancer risk using meta-analysis. Methods: A comprehensive literature search was conducted using the databases of PubMed, Web of Science, CNKI and Wanfang Data to identify the relevant publications from inception up to July 2022.The pooled relative risks(RRs) and 95% confidence intervals (CIs) were calculated for the highest versus the lowest categories of DASH score in relation to breast cancer risk, using a random-effects model. The Cochran’s Q test and I-squared(I2) statistic were used to detect the sources of heterogeneity among the included studies. Results: Overall, eleven studies, involving 23254 breast cancer cases and 449273 participants, were included in this systematic review and meta-analysis. Combining 16 effect sizes from 11 studies, a significant inverse association between adherence to the DASH diet and risk of breast cancer was observed(RR=0.79; 95%CI:0.70, 0.90, P<0.0001). Stratified analysis showed a significant association between adherence to the DASH diet and risk of breast cancer in case-control studies(RR=0.49;95%CI: 0.27-0.89, P=0.019), and a marginally significant association in prospective cohort studies(RR=0.92; 95%CI: 0.86-0.98, P=0.014), respectively. Besides, a more significant association between DASH score and reduced risk of breast cancer was observed in Asian countries (RR=0.50; 95%CI:0.31- 0.81, P=0.005) than in the United States(RR=0.93; 95%CI:0.89-0.99, P=0.012). Similarly, when we conducted analyses separately by menopausal status, we found a significant inverse association between DASH diet and breast cancer risk in postmenopausal women(RR=0.58; 95%CI:0.39-0.87, P=0.008). Conclusions:The results of this systematic review and meta-analysis indicate a significant inverse association between adherence to the DASH diet and risk of breast cancer. Further large prospective studies and randomized controlled trials are required to confirm our findings.